Development of Standard Operating Procedures (SPO) for Management of "Danger" in Emergency Patients with Anxiety Disorder - Muftikhar, Zulfian Kurniadi; Yusuf, Ah.; Rusdi, Ainur; Kurniawati, Ninuk Dian; Zamroni, Asroful Hulam (Indonesian Journal of Global Health Research, 2024)
The Emergency Unit is the first department to provide action to patients in emergencies to save lives, however patients with psychiatric anxiety disorder still receive general treatment. The Emergency Unit is the first department to provide action to patients in an emergency to save lives, however, patients with psychiatric anxiety disorders still receive general care. Therefore, this research aims to develop SOPs for handling emergency patients with anxiety disorders. Method: The research design was Research and Development carried out in 2 stages. The first phase population was 5 SOPs for emergency management. The first stage was FGD 1, divided into 3 groups, namely 17 executive nurses, 6 nursing management staff, and 2 experts (academics and practitioners). The population for the second stage of SPO development was filled by 5 nurses. The second stage was carried out FGD 2 with participants from 6 levels of nursing management. The sample used in this research was purposive sampling. The design developed is an SOP for the management of emergency patients with anxiety disorder. The analysis uses the CVI and KR20 tests. Results: There ware no SOPs for handling emergency patients with anxiety disorders. The development of SPO combines psychiatric emergency management in the form of environmental manipulation, verbal de-escalation, mechanical fixation, and pharmacological intervention with medical emergency management procedures including primary survey (airway, breathing, circulation, disability). The validity results show the CVI test is 0.8-1 and the KR20 is 0.83. Research recommendations that the development of SPO can be applied in the treatment of emergency patients with anxiety disorder. Conclusion: The development of SPO is declared to be valid and reliable in categories both in terms of functionality, efficiency, and usability, so it is recommended that nurses use it to improve the quality of hospital services.